2011
DOI: 10.1097/ico.0b013e31821de383
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Osmolarity Measurements in Dry Eye Disease Using Electrical Impedance Technology

Abstract: Our results approved the referent value in moderate to severe dry eye of approximately 316 mOsmol/L, as described in the literature. The results showed a significantly higher tear film osmolarity in patients with severe keratoconjunctivitis sicca compared with the healthy controls. Testing tear film osmolarity can be a very effective objective diagnostic tool in the diagnosis of dry eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 26 publications
4
80
1
8
Order By: Relevance
“…Although some published studies have demonstrated that normal subjects may have higher tear osmolarity values than dry eye patients, 14,15 other studies' results showed that the tear hyperosmolarity can be interpreted as an indicator of DED with good sensitivity and specificity. 7,[16][17][18] In our study, we agreed about the importance of tear hyperosmolarity in DED and we also showed that tear osmolarity is significantly higher in severe DED group than in moderate DED group. This may be interpreted as the tear osmolarity correlates with the DED severity, and it can be integrated into the DEWS grading system.…”
Section: Discussionsupporting
confidence: 85%
“…Although some published studies have demonstrated that normal subjects may have higher tear osmolarity values than dry eye patients, 14,15 other studies' results showed that the tear hyperosmolarity can be interpreted as an indicator of DED with good sensitivity and specificity. 7,[16][17][18] In our study, we agreed about the importance of tear hyperosmolarity in DED and we also showed that tear osmolarity is significantly higher in severe DED group than in moderate DED group. This may be interpreted as the tear osmolarity correlates with the DED severity, and it can be integrated into the DEWS grading system.…”
Section: Discussionsupporting
confidence: 85%
“…These are among the most common tests used in the clinical setting [38]. However, in light of the evidence concerning the lack of a relationship between symptoms and these dry eye clinical tests, more studies are needed to confirm the relationship between symptoms and other more objective diagnostic tools, such as tear film osmolarity test [39] and the double-pass scattering test [40]. In conclusion, symptoms of DED have a moderate impact on vision-related quality of life in patients with SSc, and do not correlate well with clinical findings.…”
Section: Discussionmentioning
confidence: 98%
“…60,61 Healthy humans have a median tear osmolarity of 301 mOsm/L, with a 50% CR (25th to 75th percentile) of 298 to 304 mOsm/L. 62 Repeated measurements in healthy human subjects have little variability. 60 Results of the present study revealed that tear osmolarity in healthy cats (median, 322 mOsm/L; 95% CR, 297 to 364 mOsm/L) is higher than that in humans but similar to that reported in a study 20 of 74 eyes from healthy cats (mean ± SD, 328.5 ± 17.94 mOsm/L).…”
Section: Discussionmentioning
confidence: 99%